(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2024)
The article analyzes the changes in the initial training of secondary school teachers based on three educational reforms implemented in federal higher normal schools from the nineties of the last century to the current government. The study of educational reforms places emphasis on changes or reconfigurations of an academic, institutional, organizational and political nature that affect the initial preparation of higher normal schools. Using the perspective of the public policy regime and through documentary research and testimonies of federal officials immersed in teacher training, we investigate the changes and/or permanence in the higher normal schools, which faced severe difficulties in meeting the growing demand for educators for secondary education, immersed in a whirlwind of political decisions. Among the main findings are that the three educational reforms were anchored in political-institutional arrangements that determined incremental and non-incremental changes whose effects on the training policy regime triggered counterproductive and pernicious results for the training institutions. Keywords: Teacher training. Secondary education. Higher normal education subsystem. Policy regime. Change in/of policies.